Design and Construction of a Web-Based Maintenance Ticket System to Optimize Damage Monitoring in Retail Stores - Andrianto Andrianto; Sukmawati Anggraeni Putri (GWS Tech Solution, 2025)
PT Indomarco Prismatama Tangerang 1 branch faces challenges in managing store infrastructure maintenance tickets because the reporting process is still manual. This causes delays in handling, unstructured documentation, and difficulty in monitoring repair status. This study aims to design a web-based maintenance ticket information system to improve reporting and damage monitoring efficiency. The research methods include observation, interviews, and literature study using a system development approach based on the Waterfall model. The system is developed using PHP and MySQL and designed using ERD and logical data structure modeling. Testing is performed using black-box testing and User Acceptance Testing to evaluate system functionality and user acceptance. The results show that all system functions operate properly and the system is accepted with a high level of user satisfaction. The implementation improves maintenance process effectiveness and supports smoother store operational activities.